2019
DOI: 10.1111/ecc.13174
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a counselling programme for fertility preservation in female cancer patients: The experience of the GEMME DORMIENTI network

Abstract: Objective: To describe a population of patients referred for fertility preservation (FP), how to efficiently provide FP care, and how FP care changed over time. Methods: This longitudinal observational study enrolled 281 female cancer patients referred between 2013 and 2016 to the non-profit organisation Gemme Dormienti ONLUS (GD) for FP care. All patients underwent the same battery of instrumental and laboratory diagnostic tests. GnRHa therapy was started at least seven days before CTh treatment. Results: Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“… 23 Consideration should be given to stimulation for preservation as soon as possible in patients despite ongoing treatment, as AMH decreases and follicle-stimulating hormone (FSH) increases at 1, 6, 12, 24, and 36 months following chemotherapy. 24 , 25 Providers may find the American Society for Clinical Oncology (ASCO) recommendations on fertility preservation and risk of permanent amenorrhea helpful when counseling patients. 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Consideration should be given to stimulation for preservation as soon as possible in patients despite ongoing treatment, as AMH decreases and follicle-stimulating hormone (FSH) increases at 1, 6, 12, 24, and 36 months following chemotherapy. 24 , 25 Providers may find the American Society for Clinical Oncology (ASCO) recommendations on fertility preservation and risk of permanent amenorrhea helpful when counseling patients. 26 …”
Section: Resultsmentioning
confidence: 99%
“…Success in treating cancer has created a new focus on the quality of life after cancer, and therefore, a demand for quality fertility preservation care. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that fragmentation of ovaries induced a transient increase in the polymerization of G-actin to Factin, decrease in phospho-YAP levels, and increase in nuclear localization of YAP, resulting in the upregulation of downstream CCN growth factors and baculoviral inhibitors of apoptosis repeat containing (BIRC) apoptosis inhibitors. Fragmentation of ovarian cortex into small cubes changed cytoskeletal actin dynamics and induced disruption of the Hippo signaling pathway, leading to the production of CCN growth factors and anti-apoptotic BIRC [16]. Because there is a tumor suppressor pathway in the human body that can regulate the size of organs, the imbalance of this pathway will lead to the growth of tissues and organs.…”
Section: Mechanism Of Ovarian Tissue Activation After Thawingmentioning
confidence: 99%
“…To overcome this problem, alternative approaches have been developed, either to avoid COS by cryopreservation of immature oocytes or oocytes matured in vitro or to start it at any time using a random start protocol requiring at least two 2 weeks of treatment (23). Ovarian tissue cryopreservation has also been proven to be effective for ovarian function recovery, and since 2019 is no longer been considered experimental (24).…”
Section: Introductionmentioning
confidence: 99%